The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1029/2020gl092108
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond Electromagnetic Pulses Generated by Electric Discharges: Observation With Clouds of Charged Water Droplets and Implications for Lightning

Abstract: Effects of lightning‐induced generation of high‐frequency and microwave radiation are of great interest for studying fundamental physics of lightning and its applications for monitoring of the thunderstorm activity and protection of equipment against electromagnetic interference. Ultrawideband electromagnetic pulses (UWB EMPs) of spark discharges about 1 m long were detected in a frequency band of up to 10 GHz in laboratory experiments using a cloud of water droplets charged up to the electric potential exceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…It is shown experimentally that at some phases of long electric spark development a radio-frequency emission is generated in a band of at least up to 1.4 GHz. The obtained results match with both the published natural data on radio-frequency emission of lightning [4] and the theoretical calculations [3] and measured parameters of RF emission of long streamers [6].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…It is shown experimentally that at some phases of long electric spark development a radio-frequency emission is generated in a band of at least up to 1.4 GHz. The obtained results match with both the published natural data on radio-frequency emission of lightning [4] and the theoretical calculations [3] and measured parameters of RF emission of long streamers [6].…”
supporting
confidence: 87%
“…In [3][4][5] the RF emission of real thunderstorm clouds and lightning discharges was studied. In [6] it was found that from discharges in a charged aerosol structure (simulating a thunderstorm cell) a RF emission is generated with a frequency of up to 10 GHz.…”
mentioning
confidence: 99%
“…Both of these electromagnetic radiation formation mechanisms correlate to the characteristic frequency ranges of the wavelet spectrums of signals, and are guided on model rods and long elements of the neighboring flash of the streamer corona; these develop from another model element belonging to group II and group III, containing large force-strength factors of the electric field. Electromagnetic radiation with frequencies exceeding 1 GHz during streamer flashes in the electric field of a cloud charged with water drops was registered in [28] as well.…”
Section: Analysis Of Results and Discussionmentioning
confidence: 96%
“…To measure pulsed electric and magnetic fields in the line directly, strip-line IPPL probes [25] and inductive TPMP probes with the rise time of the pulse characteristic being not more than 35 ps, respectively, were used. An assembly of such probes was used, e.g., to detect the shape of subnanosecond pulses generated by long spark discharges [26]. To detect the shape of an EMP after it passed through the plasma-filled line, the low-inductance dummy load with wideband attenuators was used.…”
Section: Large-scale Coaxial Linementioning
confidence: 99%